2017
DOI: 10.3126/ajms.v8i1.14740
|View full text |Cite
|
Sign up to set email alerts
|

Determination of errors that compromise the quality of laboratory service in a tertiary hospital

Abstract: Background:Clinical Laboratory testing is a highly complex process that entails numerous procedures. Although it has been known that laboratory testing services are safe, it is increasingly becoming a common knowledge that they are not that safe. Studies have indicated that there are a number of errors that occur due to laboratory testing processes. These errors may not be realized easily during the testing process, but they make significant impact on the results given. Aims and Objective: To determine the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This finding was far higher than the study conducted in Kenya (13.1%). 49 This may be related to non-committed laboratory staffs, the workload of the laboratory and failure to adhere to the laboratory quality policy. In addition, 1.1% of laboratory results were reported out of the established TAT, which was higher than the frequency of delayed TAT in Pakistan (0.003%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was far higher than the study conducted in Kenya (13.1%). 49 This may be related to non-committed laboratory staffs, the workload of the laboratory and failure to adhere to the laboratory quality policy. In addition, 1.1% of laboratory results were reported out of the established TAT, which was higher than the frequency of delayed TAT in Pakistan (0.003%).…”
Section: Discussionmentioning
confidence: 99%
“…Bonini et al [5] found that pre-analytical errors predominated and accounted for 31.6% to 67%. A study in Kenya [6] looking at errors during the three phases of laboratory testing found that preanalytical errors were most common with a frequency of 148 (42.8%), followed by analytical errors 114 (32.9%) and post analytical errors 84 (24.3%). In this study request forms lacking the address accounted for 27.0% of the pre-analytical errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, several African countries have documented tremendous laboratory errors. For example, a hospital in Ethiopia, Addis Ababa, reported up to 33.1% overall laboratory errors and in Kenya, Kenyatta Hospital reported up to 42% ( Tadesse, Desta, Kinde, Hassen, & Gize 2018;Kimengech, Waithaka, Onyuka, & Kigondu 2017). In order to provide quality laboratory data, international health organizations such as World Health Organization's Regional Office for Africa (WHO AFRO), Centers for Disease Control and Prevention (CDC), and American Society for Clinical Pathology (ASCP) have developed laboratory Quality Management Systems (QMS) as one of the systems used to provide laboratory quality (World Health Organization, 2011).…”
Section: Introductionmentioning
confidence: 99%